Risk Assessment of Water Quantity and Quality Stressors to Balance the Use and Protection of Vulnerable Water Resources. (3rd December 2020) - Wade, Melissa; O'Brien, Gordon C; Wepener, Victor; Jewitt, Graham
ABSTRACT: In developing regions of the world, valuable and vulnerable water resources are being used excessively. Through water resource development, multiple water quality, flow, and other stressors threaten the sustainable use and protection of these resources. Few attempts have been made to evaluate the synergistic effects of multiple water quality and flow stressors to socioecological attributes of systems that we care about in integrated water resource management. Regional scale ecological risk assessments evaluate the probable negative effects of multiple stressors, affecting dynamic ecosystems on multiple spatial scales. The present study demonstrates how multiple water quality, flow, and other stressors that cumulatively affect the sustainability of the lower Thukela River, South Africa, can be evaluated using the relative risk model, Bayesian network (RRM‐BN) approach. This risk assessment facilitated the establishment of minimum water quality and flow requirements to maintain the sustainability of this system and make water resource use and protection trade‐off decisions. In this case study, the risk of 10 water resources use and protection scenarios were evaluated in a regional scale ecological risk assessment of the socioecological attributes of the lower Thukela River. In addition we evaluated the consequences associated with these scenarios based on risk pathways of multiple sources, stressors, and receptors to endpoints that represent the sustainable vision of multiple stakeholders of the system. The outcomes of the present study have contributed to new evidence to improve the water resource use efficiency and protect important resources of the lower Thukela River, to ensure sustainability. Integr Environ Assess Manag 2021;17:110–130. © 2020 SETAC KEY POINTS: This application of the regional scale ecological risk assessment approach demonstrates how multiple stressors affecting dynamic water resources can be evaluated in a holistic manner to contribute to sustainable resource management. The application of the regional scale ecological risk assessment approach to the lower Thukela River, South Africa, contributes to an improved environmental performance of an industrial water resource user in a vulnerable socioecological system. The regional scale ecological risk assessment can be used to evaluate the relative risk of multiple stressors to social and ecological features that we care about in dynamic water resources in developing regions of the world. The regional scale ecological risk assessment has successfully been used to contribute to water resource trade‐off decisions and management between the use and protection of vulnerable water resources and the communities who depend on them in Africa.